2016
DOI: 10.5306/wjco.v7.i2.200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the microbiome in non-gastrointestinal cancers

Abstract: "The forgotten organ", the human microbiome, comprises a community of microorganisms that colonizes various sites of the human body. Through coevolution of bacteria, archaea and fungi with the human host over thousands of years, a complex host-microbiome relationship emerged in which many functions, including metabolism and immune responses, became codependent. This coupling becomes evident when disruption in the microbiome composition, termed dysbiosis, is mirrored by the development of pathologies in the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 150 publications
0
35
0
3
Order By: Relevance
“…As such, it has the foremost metabolic effect of all microbiomes. As the most frequently investigated organ system, the gastrointestinal tract has been used as a model for understanding the host-microbiota and disease relationship (Pevsner-Fischer et al, 2016;Schwabe & Jobin, 2013). Other organs, such as the skin, oral cavity and female genital tract, that also contain a considerable number of microorganisms have been less frequently studied (Schwabe & Jobin, 2013).…”
Section: Types Of Cancer That Are Considered Related To Microbiome Dymentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it has the foremost metabolic effect of all microbiomes. As the most frequently investigated organ system, the gastrointestinal tract has been used as a model for understanding the host-microbiota and disease relationship (Pevsner-Fischer et al, 2016;Schwabe & Jobin, 2013). Other organs, such as the skin, oral cavity and female genital tract, that also contain a considerable number of microorganisms have been less frequently studied (Schwabe & Jobin, 2013).…”
Section: Types Of Cancer That Are Considered Related To Microbiome Dymentioning
confidence: 99%
“…Furthermore, an estimated 93 283 people are expected to die of this disease. Pancreatic cancer is an aggressive malignancy, with a low rate of survival and therapeutic success (Mitsuhashi et al, 2015;Pevsner-Fischer et al, 2016). Therefore, it is important to further understand its pathogenesis and to search for new diagnostic and therapeutic alternatives (Mitsuhashi et al, 2015;Zambirinis et al, 2014).…”
Section: Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…(214). Earlier work demonstrated that the host (e.g., gut) microbiome dynamically interacts, i.e., influences and is affected by, inflammation including pro-tumor inflammatory pathways, and that microbial dysbiosis is implicated in many tumors, notably lung carcinomas (218,219). Of note, preclinical studies have identified gut bacteria that influence tumor immunity and response to immunotherapy and chemotherapy, in addition to other seminal reports whose findings accentuate the role of the host microbiome in tumor biology, as discussed below (220)(221)(222).…”
Section: Microbiome and Tumor Immunitymentioning
confidence: 99%
“…20-22 In addition, microbial dysbiosis has also been observed in other forms of cancers including breast, lung, urogenital, and liver, which was the subject of a recent review. 23 …”
Section: Microbial Dysbiosis and Tumorigenesismentioning
confidence: 99%